2017
DOI: 10.14573/altex.1604201s
|View full text |Cite
|
Sign up to set email alerts
|

Reference compounds for alternative test methods to indicate developmental neurotoxicity (DNT) potential of chemicals: Example lists and criteria for their selection and use_suppl

Abstract: SummaryThere is a paucity of information concerning the developmental neurotoxicity (DNT) hazard posed by industrial and environmental chemicals. New testing approaches will most likely be based on batteries of alternative and complementary (non-animal) tests. As DNT is assumed to result from the modulation of fundamental neurodevelopmental processes (such as neuronal differentiation, precursor cell migration or neuronal network formation) by chemicals, the first generation of alternative DNT tests target thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 91 publications
(117 reference statements)
0
11
0
Order By: Relevance
“…Finally, ibuprofen, a non-steroidal anti-inflammatory drug (NSAID), was selected as a negative reference compound for assay development, based on the recommendations given in a recent review on reference compounds for alternative DNT test methods [92]. This is a particularly relevant compound for our study as it crosses the BBB [93], has not been demonstrated to elicit DNT, and is a drug accepted during pregnancy and for children [92]. Ibuprofen has also been used as a negative reference compound in a recent in vitro toxicity study on neural cells derived from human embryonic stem cells [94].…”
Section: Selection Of Test Chemicals From Literature Reviewmentioning
confidence: 99%
“…Finally, ibuprofen, a non-steroidal anti-inflammatory drug (NSAID), was selected as a negative reference compound for assay development, based on the recommendations given in a recent review on reference compounds for alternative DNT test methods [92]. This is a particularly relevant compound for our study as it crosses the BBB [93], has not been demonstrated to elicit DNT, and is a drug accepted during pregnancy and for children [92]. Ibuprofen has also been used as a negative reference compound in a recent in vitro toxicity study on neural cells derived from human embryonic stem cells [94].…”
Section: Selection Of Test Chemicals From Literature Reviewmentioning
confidence: 99%
“…In particular, there is an ongoing search for alternative approaches to evaluate developmental neurotoxicity to replace traditional developmental neurotoxicity testing guidelines involving whole animals (e.g., refs and ). There are several alternative approaches being considered and many include, either explicitly or implicitly, an adverse outcome pathway-like approach. , Among the key events of neurodevelopment identified in AOP approaches are proliferation, migration, differentiation, neurite outgrowth, synaptogenesis, network formation and network function, synaptic pruning, and apoptosis. , These frameworks for evaluating developmental neurotoxicity of chemicals are also relevant for assessing nanoparticles.…”
Section: Adverse Outcome Pathwaymentioning
confidence: 99%
“…155,156 Among the key events of neurodevelopment identified in AOP approaches are proliferation, migration, differentiation, neurite outgrowth, synaptogenesis, network formation and network function, synaptic pruning, and apoptosis. 157,158 These frameworks for evaluating developmental neurotoxicity of chemicals are also relevant for assessing nanoparticles.…”
Section: Molecular Initiating Event (Mie)mentioning
confidence: 99%
“…The key events of brain development covered by the in vitro methods used in ENDpoiNTs have been chosen according to the available mechanistic insights pertaining to DNT (see Figure 2) [42][43][44][45]. The experimental models employed are summarized in Table 3.…”
Section: Relevant Models and Endpoints To Test Ed-induced Dntmentioning
confidence: 99%